The Influence of Training, Motivation, and Changes in the Digital Era on Employee Competence (Literature Review) - Kesuma Wardati, Nabila Tsaniyah; Hapzi Ali (Dinasti Publisher, 2023)
The literature Review Article, Effects of Training, Motivation, and Changes in the Digital Era on Employee Competence, is a scientific article that has the aim of building a research hypothesis about the influence of variables that will be utilized in further research within the scope of Human Resource Management. The method used for writing this Literature Review article is the library research method, reference data sourced from online media such as Google Scholar and other academic online media. This literature review article results are: 1) training affects employee competency; 2) motivation influences employee competency; and 3) changes in the digital era affect employee competence.